Seasonal Variability of Essential Oil Content of Pituranthos scoparius - Kalla, Ali; Belkacemi, Djebellah; Gherraf, Noureddine; Zellagui, Amar; Messai, Laid; Ladjel, Segni; Samir, Hameurelaine; Brahim‡, Labed; Chihi, Soumia (Asian Journal of Chemistry, 2010)
Pituranthos scoparius, a native plant in North Africa was reinvestigated for its oil content using the ordinary GC-MS analysis. More than 39 compounds were identified. Analysis revealed that its oil content is time dependent. In fact, essential oil concentrations, yields, percentage of the principle components of the aerial parts were determined using two samples collected on early February and late April, respectively. The results showed important fluctuations both quantitatively and qualitatively.